CORRELATION BETWEEN THE AMOUNT OF ORGANIC MATTER AND THE ABUNDANCE OF MACROZOOBENTHOS IN THE COASTAL WATERS OF DUMAI CITY - Octalina, Fazrianty; Badrun, Yeeri; Retnawaty, Sri Fitria (Asian Journal of Aquatic Sciences, 2023)
This research was conducted in March 2022 in the Coastal Waters of Dumai City. This study aims to analyze the amount of organic matter and the abundance of macrozoobenthos and the relationship between the amount of organic matter and the abundance of macrozoobenthos. The method used is a survey method consisting of 10 stations with 2 replications at each station. And 1 station is a control station located on the north coast of North Rupat District, Bengkalis Regency. Sediment sampling was carried out in the field and then taken to the Marine Chemistry Laboratory, Riau University for analysis of organic matter and macrozoobenthos analysis. Based on a simple linear regression test, the relationship between the amount of organic matter and the abundance of macrozoobenthos obtained a correlation value (r) = -0. 4637 with the mathematical equation y = -4.884x + 98.896. The test results show a weak and inverse relationship between the amount of organic matter and the abundance of macrozoobenthos. This means that with the increase in the amount of organic matter, the abundance of macrozoobenthos in the coastal waters of Dumai City will decrease. The value of the coefficient of determination (R2) is 0.2146. This figure shows that the